Analisis Tingkat Pemahaman Mahasiswa Universitas Negeri Medan PSPK 23 B Terhadap Soal Teori Atom - Freddy Tua Musa Panggabean; Dimas Ridho; Christy Chirona Veronika; Siti Zahara; Happy Glory Maritoma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the level of understanding of PSPK 23 B students at Medan State University on atomic theory questions. With a quantitative descriptive approach, data were collected through multiple-choice tests filled out by 30 students. The results showed an average understanding of 75.33%, which is quite good. However, there was significant variation where some students mastered basic concepts (eg Dalton and Thomson's atomic models), while others had difficulty with abstract topics (eg Bohr's model and quantum mechanics). This finding is in line with previous studies on misconceptions in atomic structure. This study emphasizes the importance of innovative learning strategies, such as visual media and conceptual approaches, to improve student understanding. Periodic evaluation is needed to detect learning gaps and adjust teaching methods. The results of this study can be a basis for developing more effective chemistry education practices.